Drug delivery to the intestinal lymph by oral formulations. (7th February 2022) - Yoshida, Takayuki; Kojima, Hiroyuki; Sako, Kazuhiro; Kondo, Hiromu
Abstract: Oral drug delivery systems (DDS) targeting lymphocytes in intestinal lymphatic vessels, ducts, and nodes are useful for treating diverse diseases. The intestinal lymph harbors numerous lymphocyte subsets, and DDS containing lipids such as triglycerides and fatty acids can deliver drugs to the lymph through the chylomicron pathway. DDS are efficient, thus allowing the administration of reduced drug doses, which mitigate systemic adverse effects. Here we review orally administered lipid formulations comprising oil solutions, suspensions, micro/nanoemulsions, self-micro/nano emulsifying DDS, liposomes, micelles, solid lipid nanoparticles, and nanostructured lipid carriers for targeting drugs to the lymph. We first describe the structures of lymphatic vessels and lymph nodes and the oral absorption of lipids and drugs into the intestinal lymph. We next summarize the effects of the properties and amounts of lipids and drugs delivered into the lymph and lymphocytes, as well as their effects on drug delivery ratios of lymph to blood. Finally, we describe lymphatic DDS containing saquinavir, tacrolimus, and methotrexate, and their potency that reduces drug concentrations in blood, which are associated with systemic adverse effects. Graphical Abstract: UF0001